086 The utility of different imaging modalities in the acute evaluation of venous sinus thrombosis. Issue 3 (9th February 2012) - Rossor, A; Talbot, B; Good, C D
Abstract : Acute venous sinus thrombosis often enters into the differential diagnosis of acute thunderclap headache when sub arachnoid haemorrhage has been excluded. When the pretest probability of a sinus thrombosis is high, then multiple imaging modalities my required in the event of a negative scan. The appropriate course of action for scenarios when the pre test probability is moderate or low is less clear. To help answer this question, we performed a blinded review of all imaging modalities (CT, CTV, MR, MRV (contrast and non-contrast enhanced) in a series of 53 patients who underwent brain imaging where sinus thrombosis was mentioned on the request card. Seven out of 53 patients had a confirmed sinus thrombosis of which five underwent a plain CT, MR and non-contrast enhanced MR venogram. The sensitivity and specificity of a plain CT was 71% and 96%, for a plain MR brain it was 100% and 97% and for a non-contrast enhanced MRV it was 80% and 91%. There was no significant difference in the sensitivity or specificity for the three modalities. In summary, our data suggest that a plain MR brain scan is superior to a non-contrast enhanced MR venogram in evaluating acute venous sinus thrombosis.